Loneliness and social participation among older Japanese adults: The influence of gender on social participation - Yuri Matsuzaki; Risa Takashima; Hiroki Okada; Maki Miyajima (PLoS ONE, 2025)
Previous studies have demonstrated that social participation can alleviate loneliness; however, the specific types and characteristics of social participation that contribute to loneliness prevention remain unclear, particularly considering gender differences. In this study, we examined the gender-related influence of the types and characteristics of social participation on loneliness among older adults aged ≥65 years. A total of 381 participants (175 men and 206 women) from a regional city in Hokkaido, Japan, completed questionnaires assessing loneliness, social participation, life-space mobility, self-evaluation of abilities, and depression. Hierarchical multiple regression analysis revealed that loneliness among men was significantly associated with participation in neighborhood association activities, group exercise, and depression, suggesting that maintaining social roles and responsibilities through these activities is essential for reducing loneliness. In contrast, for women, no specific type of social participation had a significant effect on loneliness. However, correlation analysis indicated that women’s loneliness was related to a broader range of social participation compared to that of men. These findings suggest that, for women, the extent of participation across various types of social participation is more important than engaging in specific types. Providing accessible opportunities for diverse forms of participation may be particularly effective in reducing loneliness among women. This study highlights the importance of developing gender-specific interventions to prevent loneliness. Tailored support strategies that consider the differing social roles, patterns of participation, and needs of men and women are necessary to effectively address loneliness among older adults.